A Systematic Mapping Study on Service Oriented Computing in the Context of Quality of Services - Mendonça, Danilo Filgueira; Rodrigues, Genaína Nunes; Favacho, Aletéia; Holanda, Maristela (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2013: Anais do VII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2013)
Background: In the last years, the field of service oriented computing (SOC) has received a growing interest from researchers and practitioners, particularly with respect to quality of service (QoS).Aim: This paper presents a mapping study to aggregate literature in this field in order to find trends and research opportunities regarding QoS in SOC.Method: Following well established mapping study protocol, we collected data from major digital libraries and analysed 364 papers aided by a tool developed for this purpose.Results: With respect to SOC contributions dealing with QoS properties, we were able to find out which SOC as well as which QoS facets are the focus of research. Our mapping was also able to identify those research groups that have mostly published in the context of our study. Conclusions: Most of the studies concentrate on runtime issues, such as monitoring and adaptation. Besides, an expressive amount of papers focused on metrics, computational models or languages for the context of Qos in SOC. Regarding quality attributes, a vast majority of the papers use generic models, so that the proposed solutions are independent of the particularities of a quality attribute. In spite of that, our study reveal that availability, performance and reliability were the major highlights. With respect to research type, many of the reviewed studies propose new solutions, instead of evaluating and validating existing proposals -- a symptom of a field that still needs established research paradigms.